2014
DOI: 10.1182/blood-2014-06-584656
|View full text |Cite
|
Sign up to set email alerts
|

TNF-mediated inflammation represses GATA1 and activates p38 MAP kinase in RPS19-deficient hematopoietic progenitors

Abstract: Key Points• GATA1 is downregulated in RPS19-deficient cells and zebrafish through upregulation of p53, TNF-a, and p38 MAPK.• Treatment of rps19-deficient zebrafish with the TNF-a inhibitor etanercept rescues their erythroid and developmental defects.Diamond-Blackfan anemia (DBA) is an inherited disorder characterized by defects in erythropoiesis, congenital abnormalities, and predisposition to cancer. Approximately 25% of DBA patients have a mutation in RPS19, which encodes a component of the 40S ribosomal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 28 publications
7
68
0
Order By: Relevance
“…Together, our results are reminiscent of the recent discovery that ribosomal gene mutations in Diamond-Blackfan anemia (DBA) lead to reduced GATA1 translation (17,18). Indeed, we observed that knockdown of RPS14 in SET2 cells led to a reduction in GATA1 protein (Supplemental Figure 13A).…”
Section: Resultssupporting
confidence: 61%
“…Together, our results are reminiscent of the recent discovery that ribosomal gene mutations in Diamond-Blackfan anemia (DBA) lead to reduced GATA1 translation (17,18). Indeed, we observed that knockdown of RPS14 in SET2 cells led to a reduction in GATA1 protein (Supplemental Figure 13A).…”
Section: Resultssupporting
confidence: 61%
“…Other pathways may be involved and indeed, it has been recently shown in shRNA-RPS19 deficient erythroid progenitors that the activation of tumor necrosis factor a (TNF-a) through p38 MAPK phosphorylation could play a role in decreased GATA1 expression. 45 TNF-a acting via S100A8 and S100A9 proteins of the innate immune system has recently been shown to be involved in the 5q-MDSs. 46 We cannot exclude the possibility that 1 or more additional factors interacting with HSP70 depending on the specific RP mutated gene may be modulating the different phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In patients bearing a RPS19 deficiency, the levels of GATA1 were found to be reduced in the erythroid progenitor population while p53 and TNFα expression were increased in the non-erythroid progenitors [18,20] . Inhibition of TNFα in a zebrafish model of RPS19-deficiency was able to rescue the observed anemia, suggesting TNFα expression has a significant role in the observed phenotype [20] .…”
Section: Diamond-blackfan Anemia (Dba)mentioning
confidence: 99%
“…In addition, an innate immune component has been observed. RP loss/reduction enhances the expression of innate immune genes including interferon and TNFα, which is known to contribute to the hematopoietic failure in RPS19 deficiency, likely through IRES-mediated translation [20] . Moreover, RP depletion affects the insulin signaling pathway [70] .…”
Section: Ribosomal Subunit Proteins (Rps)mentioning
confidence: 99%
See 1 more Smart Citation